Development of the Chinese Dual Auroral Radar Network and Preliminary Results - Jiaojiao Zhang; Ailan Lan; Jingye Yan; Xiang Deng; Wei Wang; Hang Li; Lingchen Sun; Ying Nan; Xiaochao Song; Chi Wang (Space Weather)
Abstract Led by the National Space Science Center of the Chinese Academy of Sciences, we have built a Chinese dual auroral radar network in northern China, which is called the CN‐DARN. The CN‐DARN consists of three pairs of high‐frequency coherent scattering radar facilities and is one of the key parts of the Chinese Meridian Project Phase II. It has been fully constructed and started trial operations at the end of 2023. The detection range of the radar network extends longitudinally over approximately 9 hr of local times and covers the middle to high latitudes of the entire Asia region above 40°. In this paper, we present the basic design of the CN‐DARN and its preliminary observations of ionospheric irregularities, subauroral polarization streams (SAPSs) and traveling ionospheric disturbances (TIDs). We also investigate its contribution to the ionospheric convection pattern of the Northern Hemisphere derived from Super Dual Auroral Radar Network (SuperDARN) observations. The results indicate that the CN‐DARN provides excellent measurements and better specifications of flows in the Asian sector, improving our understanding of the global‐scale ionospheric convection pattern in the Northern Hemisphere. These encouraging results lead us to believe that the CN‐DARN will play an important role in studies on the evolution of ionospheric irregularities, the characteristics and evolution of SAPSs, the propagation of TIDs, and global‐scale ionospheric convection dynamics.